Teaching strategies and development of creativity in education - Aquije-Mansilla, María Elizabeth; Rios, Teresa Chara-De los; Solis-Trujillo, Beymar Pedro; Pérez-Ruiz, Jhon Christian (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the role of education in a global context, emphasizing creativity as a key component for preparing new generations to face future challenges. It highlights international commitments such as the Incheon Declaration for Education 2030, which advocates for inclusive and quality learning opportunities. Systematic reviews synthesize findings from multiple sources, providing a comprehensive and robust perspective on the topic. This method allows for a deeper understanding of the theoretical foundations of creativity in education, particularly through models such as Guilford’s framework and the 4P's of creativity. The review identified creativity as a fundamental element in education, structured around key aspects such as fluidity, flexibility, originality, and elaboration. The findings emphasize the importance of fostering creativity within educational environments to enhance learning opportunities and problem-solving skills. Creativity plays a crucial role in modern education, helping students develop essential competencies for the evolving global landscape. Integrating creativity-focused models can improve learning outcomes and better prepare students for future professional and personal challenges. Educational institutions and policymakers should incorporate creativity-driven frameworks into curricula and teaching methodologies. Emphasizing creativity can lead to more engaging and effective learning experiences, fostering innovation and adaptability among students.